(3GdJCejf h EOGQI GdNWQ (B:s (3GdfXQjI h GdJWHjb (B/s - (3YQjbGJ, MQHj eMeOs; (3Ybd, SYjO LeYIs ((3YeGf(B: s (3OGQ hGFd(B, s, 2010)
(3GdNWQ , eaGgje GdJCejf h hXGFag GdGQcGf h GdeHGOF GdbGfhfjI dYbO GdJGejf , CfhGY GdJGejfGJ GdYGeI (B( (3GdeeJdcGJ h GdeSDhdjI GdeOfjI (B) (3, GdJCejf GdHMQj , JGejf GdSjGQGJ , GYGOI GdJCejf , GdJGejf GdGSdGej , CbSGW GdJCejf h GdGMJjGWGJ , GdJShjb GdJCejfj , GdVeGf GdGLJeGYj , GdJCejf GdUMj h GdJCejf Ydi GdMjGI , GdTQhW GdGSGSjI dHhdjUI GdJCejf Ydi GdMjGI , CfhGY GdJCejfGJ Ydi GdMjGI , JWhQ h gjcd Shb GdJCejf aj GdGQOfs
Keywords: (3GdJCejf (B- (3GdHfhcs; (3GdJCejf(B- (3GdCQOfs; (3GdJCejf(B- (3GdeNGWQs